Ekstraksi Na-Alginat dari Rumput Laut Padina sp. Menggunakan Konsentrasi Kalium Hidroksida yang Berbeda - Elza Septiani; Ginanjar Pratama; Raja Marwita Sari Putri (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2017)
The objective of this study was to obtain the best sodium alginate extract from Padina sp. with different potassium hydroxide concentration. Padina sp. was collected in coastal Senggarang, Tanjungpinang, Riau Islands Province. The raw material of Padina sp. was extraction by potassium hydroxide with different concentration (0.6%, 0.8%, 1%).  We analyzed content of moisture, ash, yield, viscosity and pH. The best results obtained in the treatment with  a solution of KOH concentration 0,8% with content of moisture 10,87%, ash 31,24%, yield 17,82%, viscosity 275,50 cP and pH 8,21.